Application of Decision Tree Algorithm for Classification of Rice Yields in Sumatra - wily candra (PT. Visi Media Network, 2024)
Rice is the main food crop in Indonesia, most of the agricultural sector in Indonesia is dominated by rice farming including on the island of Sumatra. A common problem that arises is how to find out the areas that produce the most rice each year on the island of Sumatra. This study aims to classify the areas that produce the most rice on the island of Sumatra. The dataset used in this study was taken from Kaggle with a total of 225 data and will be tested using the Decision Tree algorithm and several other algorithms. For data visualization, Tableau will be used to see which areas produce the most rice on the island of Sumatra. By using the research method using the Decision Tree algorithm, an accuracy of 97.78% was obtained with a data split of 0.8 for training data and 0.2 for testing data.